Challenges faced by 1st phase MBBS students during online teaching of competency-based medical education curriculum - COVID times - B Persis Sofia; S Cynthia Subhaprada (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Competency-based medical education (CBME) is a learner-centered, outcome-based approach which motivates self-learning. Currently, the world is experiencing COVID-19 pandemic which led to shutdown of colleges, and hence, online teaching has become a key component in the continuity of medical education. The main aim of the study is to analyze the impact of COVID-19 pandemic on online teaching among 1st-year MBBS students and to assess the challenges faced during this time. METHODS: After obtaining institutional ethics committee clearance, a mixed-method study design was used to collect data from 100 respondents among 1st-year MBBS students of Kurnool Medical College, Kurnool, during the month of September 2020. A prevalidated, semi-structured questionnaire was sent to the participants through Google Forms. The quantitative analysis was done through survey questions on a five-point Likert scale. RESULTS: The reported challenges to online medical education during COVID-19 pandemic were lack of in-person communication (57%), technical issues while attending online classes (49%), difficulty in time management (50%), confusion in understanding course expectations/competencies (44%), and more focused on theory than practicals (59%). Some of them stated that "having online classes is really helpful than not having any classes at all." CONCLUSIONS: Hence, we conclude that though challenges mentioned above were faced during online teaching of CBME curriculum, effective leadership and student teamwork would be helpful in successful online teaching.